Drawing Education - Worldwide! Continuities - Transfers - Mixtures - Nanobashvili, Nino; Teutenberg, Tobias (Heidelberg University Publishing (heiUP), 2019)
As a cultural technique, drawing was firmly anchored in the realities of European society from early modern to modern times. Based on this fact, the present volume asks for the first time about the significance of drawing and drawing education in other cultural areas. Indigenous methods of drawing and sign-learning in Arabic, Asian, Latin American, North American and European countries are addressed as well as historical transfer processes of didactic methods, aesthetic norms and educational institutions of drawing instruction.